Science Communication in Poland – summary (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
Science communication is a dynamic, global phenomenon that has evolved from a model of knowledge dissemination to a participatory model of knowledge co-creation, from a field based solely on traditional media to one that increasingly uses the Internet and digital media technologies. Contemporary research shows that, on the one hand, its participants only believe in science that is consistent with their beliefs and, some even claim that their lives would not change if science did not exist. On the other hand, in the same research reports, one can read that trust in science and scientists increased in 2020. According to the editors of this monograph, this increase in trust and the fall in sceptical attitudes is influenced by science communication, the foundations of which are dialogue with citizens, an inclusive approach to the research initiatives, the promotion of citizen science, and building relationships based on trust. The readiness of Polish society to enter into a dialogue with scientists is a promising prognosis for the development and dissemination of science communication in our country. It will make it possible to broaden the circle of stakeholders, create a basis for increased individual and systemic activity, and fight for more intense development of the science communication culture. One of the first such activities was the CONCISE project, the results of which are presented in this book and summarised in the final chapter.